A Comparative Study Between Concentric Single-Needle Puncture Technique and Conventional 2-Needle Technique for Temporomandibular Joint Arthrocentesis Plus Corticosteroid Injections. Issue 2 (June 2020) - Kumar, Amit; Gupta, Amit; Ghosh, Rajarshi; Pandey, Rajeev; Kumar, Sanjeev
The purpose of the study was to compare 2 techniques of arthrocentesis, to find out the efficacy of one over the other at various parameters, and to contribute to the scarce literature of these 2 techniques. Forty patients reported with a chief complaint of pain in temporomandibular joint (TMJ), clicking in TMJ, and restricted mouth opening were included in this study. Twenty patients were divided into 2 groups, all reporting with temporomandibular disorders. Group A was treated with 2-needle technique of arthrocentesis, while group B underwent concentric needle technique of arthrocentesis under local anesthesia with Ringer's lactate solution. The operating time was found to be less in concentric needle technique (mean: 25.36 minutes) compared to 2-needle technique (mean: 42.82 minutes), and the difference was found to be statistically significant. Concentric needle technique proved to be a better alternative for TMJ arthrocentesis as it has quite a lot of advantages over 2-needle technique.